Evaluation of Community Forestry Program (HKm) at KPH Unit V Wakonti in Kaisabu Baru Village, Sorawolio District, Bau Bau City, Southeast Sulawesi Province. - Hafidah Nur (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2025)
Evaluation of community forestry program is a systematic process to assess the effectiveness, efficiency, and impact of HKm program implementation on community welfare and forest sustainability. This study aims to determine the evaluation of HKm program at KPH Unit V Wakonti in Kaisabu Baru Village. This research was conducted in Sorawolio District, Bau-Bau City, Southeast Sulawesi Province in February-March 2025, with a sample in this study of 30 people from KTH Batuawu Lestari members who were selected by purposive sampling and the population in this study was the Batuawu Lestari forest farmer group. The methods used in this study are quantitative and qualitative approaches. The data obtained were analyzed using a Likert scale. The results of the study showed that the evaluation of the program based on the institutional governance aspect of HKm was considered good by the majority of respondents with a percentage (90%), indicating the success of the organization in running this program. However, in the aspect of HKm business governance there were significant challenges with a percentage (10%) of respondents assessing that this program had not run optimally, especially in market access and management of NTFPs so that it still needed improvement in strengthening the economic aspect and market access.